2008
DOI: 10.1007/s10152-007-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton response to a warmer northern Wadden Sea

Abstract: Weekly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 28 publications
2
30
1
1
Order By: Relevance
“…There temperatures range between 8.9 and 28.2°C (Uye and Sano 1998), which is generally higher than in the studied Wadden Sea station (between -1.8 and more than 20°C (Martens and Beusekom 2008)). The warming of the Wadden Sea (Martens and Beusekom 2008) may have provided the right environment for O. davisae to settle. Reise and van Beusekom (2008) revealed that global warming is an important factor for species invasions in the Wadden Sea, since most of the introduced species originate from warmer regions than the North Sea.…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…There temperatures range between 8.9 and 28.2°C (Uye and Sano 1998), which is generally higher than in the studied Wadden Sea station (between -1.8 and more than 20°C (Martens and Beusekom 2008)). The warming of the Wadden Sea (Martens and Beusekom 2008) may have provided the right environment for O. davisae to settle. Reise and van Beusekom (2008) revealed that global warming is an important factor for species invasions in the Wadden Sea, since most of the introduced species originate from warmer regions than the North Sea.…”
Section: Resultscontrasting
confidence: 59%
“…Martens and Beusekom 2008), which is also true for its original habitat, the coastal waters of southwestern Japan (Nishida 1985;Uye and Sano 1998). There temperatures range between 8.9 and 28.2°C (Uye and Sano 1998), which is generally higher than in the studied Wadden Sea station (between -1.8 and more than 20°C (Martens and Beusekom 2008)). The warming of the Wadden Sea (Martens and Beusekom 2008) may have provided the right environment for O. davisae to settle.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations